Implementasi Identitas Nasional Sebagai Salah Satu Determinan Pembangunan Bangsa dan Karakter - Puji Tambunan; Eiykel Suranta Siboro; Jeremia A.G Sitohang; Raniko S. Maha; Sri Yunita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This research was conducted with the aim of knowing national identity, supporting factors for the birth of national identity, as well as examining efforts that can be made in maintaining national identity as one of the determinants of nation and character development. In this study using qualitative research methods. At this stage the writer seeks research data directly through interviews. This activity requires an agreement on time and place with the resource person or informant. The data collection technique used in this study was structured interviews. The recording technique is done by using notes using small notes. This type of interview aims to find hypothetical answers. Structured interviews are generally used if all research samples are deemed to have the same opportunity to answer the questions posed. The advantage of this structured interview is that there are no in-depth questions that allow lies to the informants interviewed. The basis or theory of the discussion this time is obtained from the results of literature or literature studies obtained from various relevant sources such as books, journals and articles.